1996
DOI: 10.1136/vr.138.21.511
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, location and interrelationships between the sites of abscesses recorded in pigs at a bacon factory in Northern Ireland

Abstract: The position and incidence of all the abscesses detected during post mortem inspection of 75,130 bacon weight pigs were recorded. Abscesses were detected at one site only in 2.87 per cent of the carcases examined, and at more than one site in 0.26 per cent of the carcases. Tail biting was the cause of the infection in 61.7 per cent of all the carcases with lesions at more than one site. In almost all cases there was a statistically significant interrelationship between the visible abscesses at different sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
0
6

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 6 publications
6
57
0
6
Order By: Relevance
“…The percentage increase in the visibility of mild tail lesions from SS1 to SS2 was particularly high (131.4% increase). Tail lesions, particularly more serious lesions, are related to secondary conditions such as abscessation and pleuritic lesions of the lungs (Huey, 1996;Marques et al, 2012), and are associated to a greater extent with trimming of the carcass than milder lesions (Kritas and Morrison, 2007). Nonetheless, even mild tail lesions are associated with carcass condemnations and reduced carcass weights (Harley et al, 2012a and.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The percentage increase in the visibility of mild tail lesions from SS1 to SS2 was particularly high (131.4% increase). Tail lesions, particularly more serious lesions, are related to secondary conditions such as abscessation and pleuritic lesions of the lungs (Huey, 1996;Marques et al, 2012), and are associated to a greater extent with trimming of the carcass than milder lesions (Kritas and Morrison, 2007). Nonetheless, even mild tail lesions are associated with carcass condemnations and reduced carcass weights (Harley et al, 2012a and.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, abscessation, the most common cause of partial carcass condemnation in Irish pig herds (Harley et al, 2012a), is directly related to welfare lesions. For example, infections originating in the tail can spread to other body regions via the blood stream and cerebrospinal fluid (Huey, 1996), resulting in secondary abscessation. Similarly, skin lesions can lead to the spread of secondary infection (Pluym et al, 2011) and may be the source of single-site abscessation in the limbs, flank and shoulders of pigs (Huey, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most findings were histologically classified as mild. Abscesses, previously repeatedly associated with tail lesions (Elbers et al, 1992;Huey, 1996), were rare and found in the lung (one V and two TB), the diverticle of the urinary bladder (one TB) and in the tail (one V).…”
Section: Pathologymentioning
confidence: 96%
“…Associations between tail damage and other pathological lesions have been reported repeatedly in slaughtered pigs (Elbers et al, 1992;Huey, 1996). This kind of material, however, only includes acute tail damage in -Present address: Department of Production Animal Medicine, Faculty of Veterinary Medicine, University of Helsinki, PO Box 66, FIN-00014 Helsinki, Finland.…”
Section: Introductionmentioning
confidence: 99%